Analysis of the ductility dip cracking in the nickel-base alloy welding overlay on heat exchanger tube sheet. (May 2023) - Liu, Tong; Wang, Qiongqi; Guan, Kaishu
Highlights: Macro cracks on the weld overlay are caused by the propagation of the ductility dip crack that arises during the welding process. Improper welding strategy and inappropriate choice of welding material is the root cause of ductility-dip microcrack. Few actual cases of this type of cracking are discussed in the current research papers. The mechanism and root causes of ductility dip cracking are discussed in detail. Abstract: In this paper, the cracking failure of the weld overlay of the heat exchanger tube sheet was analyzed. The weld overlay, welded by ErNiCrMo-3, cracked several times within a short period after the heat exchanger was put into operation, resulting in internal leakage from the heat exchanger. The failure causes are investigated by means of macroscopic observation, metallographic analysis, scanning electron microscope (SEM) coupled with energy dispersive spectroscopy (EDS) analysis, and hardness test. The synthetical analysis shows that a sudden drop in ductility of the weld overlay material occurs at the time of microcracking, and a phenomenon similar to grain boundary sliding is observed in the fracture morphology image at high magnification. Therefore, the microcrack on the weld overlay is a kind of ductility dip crack at elevated temperatures. Improper welding strategy and inappropriate choice of welding material is the root cause of ductility-dip microcrack during the welding process. The microcracks on the weld overlay propagate during the operation of the heat exchanger, causing it to leak several times in a short period.